Innovation on demand - Fey, Victor; Rivin, Eugene I. (Cambridge : Cambridge University Press, 2005)
'This book describes a revolutionary methodology for enhancing technological innovation called TRIZ. The TRIZ methodology is increasingly being adopted by leading corporations around the world to enhance their competitive position. The authors explain how the TRIZ methodology harnesses creative principles extracted from thousands of successful patented inventions to help you find better, more innovative solutions to your own design problems. You'll learn how to use TRIZ tools for conceptual development of novel technologies, products and manufacturing processes. In particular, you'll find out how to develop breakthrough, compromise-free design solutions and how to reliably identify next generation products and technologies. This explains the book title.
Whether you're trying to make a better beer can, find a new way to package microchips or reduce the number of parts in a lawnmower engine, this book can help. Written for practicing engineers, product managers, technology managers and engineering students.'--BOOK JACKET.
Includes bibliographical references and index.
Keywords: New products